Building Good Urban Governance Through Bureaucratic Reform: Best Practices From Surabaya, Indonesia - Bellastuti, Damaris Bernike; Suwitri, Sri (Universitas Riau Kepulauan, 2025)
Bureaucratic reform has become a strategic foundation for improving public service quality and strengthening governance in Indonesia. The city of Surabaya stands out as a leading case, achieving the highest Bureaucratic Reform Index in 2024 through consistent integration of digital innovation, human resource development, and participatory governance. This study analyzes Surabaya’s best reform practices including the Public Service Mall, the WargaKu complaint system, Surabaya Single Window, and Satu Data Surabaya and how they contribute to the realization of Good Urban Governance. Using a descriptive qualitative approach, the research draws upon secondary data from official reports, academic studies, and government evaluations. The findings show that these reforms have significantly improved efficiency, transparency, accountability, participation, and responsiveness, transforming Surabaya into a more citizen-oriented administration. Nevertheless, the reform process also faced challenges such as bureaucratic resistance, digital inequality, and inter-agency coordination gaps, which were mitigated through leadership commitment and multi-actor collaboration. The study contributes both practically by identifying replicable reform strategies for other cities and theoretically by illustrating how localized bureaucratic reform operationalizes the principles of good urban governance in developing contexts. Future research is recommended to assess the long-term sustainability and adaptability of such reforms across cities with varying administrative capacities. Surabaya’s experience demonstrates that sustainable governance is built not only through structural reform, but through continuous digital innovation, institutional learning, and citizen participation.